Plasmonics - Szoplik, Tomasz; Lavrinenko, Andrei (Photonics Letters of Poland, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 8.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This topical issue of Photonics Letters of Poland is devoted to Plasmonics. A series of 12 papers deals both with technology, as well as pure and applied physics. The other three papers are regular contributions.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>